2022
DOI: 10.1021/acs.jpcc.2c05850
|View full text |Cite
|
Sign up to set email alerts
|

Toward Bright Colloidal Near-Infrared Emitters: Surface Passivation of 2D PbSe Nanoplatelets by Metal Halides

Abstract: Colloidal 2D PbSe nanoplatelets (NPLs) are promising near- and short wave-infrared emitters for optoelectronic applications at telecommunication wavelengths. However, their photoluminescence quantum yield (PLQY) is limited by the ubiquitous presence of surface-related trap states. Here, we apply a treatment of colloidal PbSe NPLs with different metal halides (MX2, M = Zn, Cd, Pb; X = F, Cl, Br, I) to improve their emission brightness. A surface passivation of the NPLs by PbI2 leads to the best results with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…56 Biesterfelt et al observed the greatest PLQY increase of 2D PbSe NPLs after treatment with PbI 2 and the greatest PLQY decrease after treatment with CdF 2 . 23 The results for CdSe NCs presented here show that Cd-based ligands are more effective at passivating surface defects than Pb-based ligands. Thus, in both studies, the Z-type ligand native to the NC material yields the brightest NC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…56 Biesterfelt et al observed the greatest PLQY increase of 2D PbSe NPLs after treatment with PbI 2 and the greatest PLQY decrease after treatment with CdF 2 . 23 The results for CdSe NCs presented here show that Cd-based ligands are more effective at passivating surface defects than Pb-based ligands. Thus, in both studies, the Z-type ligand native to the NC material yields the brightest NC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Biersterfield and co-workers noted that CdF 2 -modified PbSe nanoplatelets (NPLs) exhibit half the PL quantum yield (PLQY) of pristine NPLs, yet the PLQY doubles for PbI 2modified NPLs. 23 Likewise, Greaney et al observed a different photoresponse between CdCl 2 -, CdBr 2 -, and CdI 2 -modified CdSe NCs. 20 Both studies highlight the potential use of nanomaterials in optoelectronic applications, but achieving trap-free nanomaterials is predicated on the judicious choice of a Z-type ligand.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infrared 2D colloidal materials are driven by narrow band gap semiconductors such as lead and mercury chalcogenides. These two classes of materials have very different growth mechanisms.…”
Section: Introductionmentioning
confidence: 99%